BILINGUALISME DAN PENGARUH PENYERAPAN BAHASA BAGI PERKEMBANGAN BAHASA ETNIS TIONGHOA DESA SUKOMORO - Agus Miftah; Resdianto Permata Raharjo; Titik Indarti (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
The emergence of language contact and conflict cannot be separated from the role of the language community. Language diversity also applies in Indonesia. This is relevant to the geographical location of Indonesia which consists of various islands, so that each community has different language characteristics. An example is the contact and language conflict of Ethnic Minorities, especially ethnic Chinese from Chinatown village in Sukomoro Village, Sukomoro District, Nganjuk Regency. This study aims to describe the phenomenon that occurs when ethnic Chinese and ethnic Javanese interact as well as the implementation of a sociolinguistic study that focuses on language contact and conflict. This type of research uses a descriptive method with a qualitative approach because it describes all phenomena in written form when the two ethnicities interact. Data collection techniques using observation or direct observation with interviews and recording activities. The data sources are the Javanese Ethnic Society and the Chinese Ethnic Minority of Sukomoro Village, relevant books, as well as references from journals. The results of this study indicate that (1) there is language contact between the Javanese and Chinese ethnic people, (2) language conflicts occur when the Javanese and ethnic Chinese interact because they still use their native language, (3) the pidgin language is a solution to overcome the problem. conversations between different ethnic languages, (4) There is a phenomenon from pidgin language into creole language that affects language development in Chinese ethnic